Japanese mothers’ utterances about agents and actions during joint picture-book reading - Murase, Toshiki (Frontiers in Psychology, 2014)
This study extended the research on the scaffolding provided by mothers while reading picture books with their children from a focus on conversational styles related to labeling to a focus on those related to agents and actions to clarify the process by which language develops from the one-word to the syntactic stage. We clarified whether mothers decreased the degree of scaffolding in their initiation of conversations, in the responses to their children’s utterances, and in the choice of referential ranges of their utterances. We also investigated whether maternal conversational styles contributed to the development of their children’s vocabularies. Eighteen pairs of Japanese mothers and their children were longitudinally observed when the children were 20 and 27 months of age. The pairs were given a picture book depicting 24 animals engaged in everyday behavior. The mothers shifted their approach in the initiation of conversation from providing to requesting information as a function of their children’s age. The proportion of maternal elaborative information-seeking responses was positively correlated with the size of their children’s productive vocabulary. In terms of referential choices, mothers broadened the range of their references as their children aged. In terms of the contribution of maternal conversational styles to children’s vocabulary development, the use of a maternal elaborative information-seeking style when the children were 20 months of age predicted the size of the children’s productive vocabulary at 27 months. These results indicate that mothers decrease the degree of scaffolding by introducing more complex information into the conversations and transferring the role of actively producing information to their children by requesting information as their children develop. The results also indicate that these conversational styles promote the development of children’s vocabularies during the transition from the one-word to the syntactic stage.